KYAUTAR КAHO A FADAR FULANI: TSOKACI DAGA FADAR KANO - Kabir , Halima Daura (International Journal of Arts, Languages, Linguistics and Literary Studies, 2023)
January 30th 2023 marks the last Presidential Visit of President Muhammadu Buhari to Kano State and Kano Palace as well. While in Kano, the President commissioned some states projects and paid homage to the Emir of Kano, Alhaji Aminu Ado Bayero, where he also commissioned a renovated mini palace called ‘Soron Ingila’; which was formally built by the eight Fulani Emir of Kano, Malam Muhammadu Abbas. As part of the tradition, the Emir presented a gift of cow horn to Mr. President which culminates into social media responses. The paper adopts historiography and interview as a source of collecting data to examine the meaning and value of gift of horn to an important dignitary in Fulɓe tradition. Findings of the research reveals how the horn was used for centuries to keep valuable items inside; such as money and bullan (traditional attire among the ruling class that was inside the horn presented to the President), and for decoration which many people including some Fulani young ones are ignorant and perhaps the reasons for the debate.